High Reflectance Nanoscale V/Sc Multilayer for Soft X-ray Water Window Region. Issue 1 (December 2017) - Huang, Qiushi; Yi, Qiang; Cao, Zhaodong; Qi, Runze; Loch, Rolf; Jonnard, Philippe; Wu, Meiyi; Giglia, Angelo; Li, Wenbin; Louis, Eric; Bijkerk, Fred; Zhang, Zhong; et al.
Abstract V/Sc multilayer is experimentally demonstrated for the first time as a high reflectance mirror for the soft X-ray water window region. It primarily works at above the Sc-L edge (λ = 3.11 nm) under near normal incidence while a second peak appears at above the V-L edge (λ = 2.42 nm) under grazing incidence. The V/Sc multilayer fabricated with a d-spacing of 1.59 nm and 30 bilayers has a smaller interface width (σ = 0.27 and 0.32 nm) than the conventional used Cr/Sc (σ = 0.28 and 0.47 nm). For V/Sc multilayer with 30 bilayers, the introduction of B4 C barrier layers has little improvement on the interface structure. As the number of bilayers increasing to 400, the growth morphology and microstructure of the V/Sc layers evolves with slightly increased crystallization. Nevertheless, the surface roughness remains to be 0.25 nm. A maximum soft X-ray reflectance of 18.4% is measured at λ = 3.129 nm at 9° off-normal incidence using the 400-bilayers V/Sc multilayer. According to the fitted model, an s-polarization reflectance of 5.2% can also be expected at λ = 2.425 nm under 40° incidence. Based on the promising experimental results, further improvement of the reflectance can be achieved by using a more stable deposition system, exploring different interface engineering methods and so on.